2012
DOI: 10.1128/aem.01296-12
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Vibrio parahaemolyticus and Vibrio vulnificus in the Coastal and Estuarine Waters of Louisiana, Maryland, Mississippi, and Washington (United States)

Abstract: f Vibrio parahaemolyticus and Vibrio vulnificus, which are native to estuaries globally, are agents of seafood-borne or wound infections, both potentially fatal. Like all vibrios autochthonous to coastal regions, their abundance varies with changes in environmental parameters. Sea surface temperature (SST), sea surface height (SSH), and chlorophyll have been shown to be predictors of zooplankton and thus factors linked to vibrio populations. The contribution of salinity, conductivity, turbidity, and dissolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
183
7
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(220 citation statements)
references
References 72 publications
(96 reference statements)
15
183
7
2
Order By: Relevance
“…In recent years, occurrences of V. parahaemolyticus have been documented as far north as Alaska, and this northward migration trend may be attributed to the rise in ocean temperature (8,9,17). Interestingly, it was demonstrated that growth in differing NaCl concentrations alters the susceptibility of V. parahaemolyticus to other environmental stresses (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, occurrences of V. parahaemolyticus have been documented as far north as Alaska, and this northward migration trend may be attributed to the rise in ocean temperature (8,9,17). Interestingly, it was demonstrated that growth in differing NaCl concentrations alters the susceptibility of V. parahaemolyticus to other environmental stresses (18).…”
mentioning
confidence: 99%
“…In the marine and estuarine environments, V. parahaemolyticus must navigate changing salinities, temperatures, and nutrient limitations and is known to proliferate during the warmer months of the year when the salinity and temperature are elevated (2,(5)(6)(7)(8)(9). Vibrio parahaemolyticus levels in marine and estuarine waters are linearly dependent on both salinity and water temperature, and in the winter, the bacterium is rarely isolated from the water column and is typically only found in small numbers in sediment (2,5,10).…”
mentioning
confidence: 99%
“…Vibrio parahaemolyticus is another bacterium that is commonly found in the coastal bay systems of the United States and Canada causing gastrointestinal illness in humans from consuming shellfish, especially oysters during the summer months (CDC, 2013). In the three coastal areas of the United States, a 21-month research conducted by Johnson et al (2012) investigated the relationship between V. parahaemolyticus and V. vulnificus in the sediment, oysters and water to the environmental quality. They found strong relationships between the Chlorophyll-a concentrations, salinity, and dissolved organic carbon concentrations.…”
Section: Eastern Oysters In Delaware Inland Bays-seafood Safetymentioning
confidence: 99%
“…Vibrio parahaemolyticus was cultivated in the laboratory from waters with a temperature of 10 • C in Mobile Bay, Alabama (DePaola et al, 2003). Johnson et al (2012) investigated relationships between environmental parameters and V. parahaemolyticus and V. vulnificus populations in water, oysters, and sediment samples in three coastal areas of the United States during a 21-month study. These authors found strong correlations between sea surface temperature and suspended particulate matter and total and potentially pathogenic V. parahaemolyticus and V. vulnificus populations.…”
Section: Case Studies-oyster Safety For Consumptionmentioning
confidence: 99%
“…The human pathogen Vibrio parahaemolyticus is commonly found associated with shellfish, particularly oysters (1,2). Depuration is a controlled process in which shellfish are placed into clean seawater to reduce the bacterial contaminants in their tissues.…”
mentioning
confidence: 99%